The Effect of Population Density on the Level of Public Awareness in 3R-Based Domestic Waste Management: A Study in the Densely Populated Settlement of Sangkrah Village, Surakarta City - Ariyanti, Nadya Putri Kus; Priyanto, Syalsabila Alfrida; Salsabila, Hasna Najla (Generasi Sains Indonesia, 2025)
The increasing population in Surakarta City, particularly in the densely populated Sangkrah Village, has contributed to an increase in the volume of domestic waste, or what we better know as household waste. Although the importance of waste management based on 3R (Reduce, Reuse, Recycle) has been frequently voiced, we still face problems such as lack of infrastructure and low community participation. Therefore, this study aims to see whether population density affects residents' awareness in managing household waste with the 3R principle in Sangkrah Village. This study used a quantitative method with a survey approach, involving 100 respondents from Sangkrah Village who were randomly selected (accidental sampling). The data obtained were analyzed using the Pearson correlation test and simple linear regression. The results show that most respondents have a fairly good understanding of the 3R concept. However, waste recycling practices in the field are still relatively ordinary. Our statistical analysis also shows that population density has no significant relationship with the level of community awareness in managing 3R waste (P-value 0.958; correlation coefficient 0.005).